Developing framework Life Cycle Cost (LCC) components to energy performance in green office buildings / Nurul Afiqah Yunus - Yunus, Nurul Afiqah (2022)
In today’s critical economy, expectations have gone beyond design and construction of a green building. The major barrier for growth in the green building market is the perception of higher first costs associated with these buildings. It has long been acknowledged that it is unacceptable to appraise the costs of projects only on the basis of their initial costs. Hence, Life-Cycle Cost (LCC) is beneficial in allowing owners and clients to make an informed decision on the building materials. Through LCC, the total ownership of cost that includes operation and maintenance costs for a building items calculated in the design stage to get a more accurate projection for entire building life cycle. Ideally, the criteria or components of LCC should be determined before deciding to proceed with the project. However, the LCC components for green projects are fragmented and the items are not kept in a proper system. This situation can be challenging for the decision makers to adopt LCC exercise as there is no proper guidance on the LCC components for green projects. Hence, this research aims to develop the framework of LCC components to energy performance active design in green office buildings. The objectives of this research are to identify the life cycle cost (LCC) components to the energy performance for active design in green office buildings, to analyse the level of importance life cycle cost (LCC) component to energy performance active design in green office buildings and to develop the framework of life cycle cost (LCC) component of energy performance active design in green office buildings. A quantitative approach was used in this research by using questionnaire survey as the main instrument.